Wilson’s Disease: An Inherited, Silent, Copper Intoxication Disease - Uta Merle; Ralf Weiskirchen (European Medical Journal Neurology, 2016)
Wilson’s disease is a rare, autosomal recessive, genetic, copper overload disease, which evokes multiple motor or neuropsychiatric symptoms and liver disease. It is the consequence of a variety of different mutations affecting the ATP7B gene. This gene encodes for a class IB, P-type, copper-transporting ATPase, which is located in the trans-Golgi network of the liver and brain, and mediates the excretion of excess copper into the bile. When functionally inactive, the excess copper is deposited in the liver, brain, and other tissues. Free copper induces oxidative stress, lipid peroxidation, and lowers the apoptotic threshold of the cell. The symptoms in affected persons can vary widely and usually appear between the ages of 6 years and 20 years, but there are also cases in which the disease manifests in advanced age. In this review, we discuss the considerations in diagnosis, clinical management, and treatment of Wilson’s disease. In addition, we highlight experimental efforts that address the pathogenesis of Wilson’s disease in ATP7B deficient mice, novel analytical techniques that will improve the diagnosis at an early stage of disease onset, and treatment results with copper-chelating agents.